2015
DOI: 10.1007/s10681-015-1457-5
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a major QTL for hairy leaf sheath introgressed from Aegilops tauschii and its association with enhanced grain yield in bread wheat

Abstract: Aegilops tauschii, the diploid D genome progenitor of the hexaploid wheat, has been used to improve modern common wheat by creating synthetic hexaploid wheat (SHW) as a bridging mechanism for wheat breeding. Most Ae. tauschii accessions have hairiness on the leaf sheath, whereas the hexaploid common wheat is usually glabrous. In this study a major QTL for leaf sheath hairiness (LSH) was detected on the long arm of chromosome 4D in two recombinant inbred line (RIL) populations produced from SHW-derived cultivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…A major QTL on 4DL associated with leaf sheath hairiness in a synthetic derivative of the wheat variety Chuanmai42 was identified, and its wild allele was found to have originated from Ae. tauschii, which has significantly increased grain weight, grain yield, and yield-related characters [20].…”
Section: Introductionmentioning
confidence: 99%
“…A major QTL on 4DL associated with leaf sheath hairiness in a synthetic derivative of the wheat variety Chuanmai42 was identified, and its wild allele was found to have originated from Ae. tauschii, which has significantly increased grain weight, grain yield, and yield-related characters [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ae. tauschii is a widely distributed (van Slageren, 1994) and genetically diverse species (Lubbers et al, 1991; Dvorak et al, 1998; Schneider et al, 2008), with superiority in resistance to disease, pest and tolerance to environmental stresses, which could be expressed in a hexaploid genetic background, as lots of related QTLs or genes had been mapped to D genome of synthetic wheat (Nkongolo et al, 1991; Innes and Kerber, 1994; Cox and Hatchett, 1994; Thompson and Haak, 1997; Yang et al, 2003; Zhu et al, 2005; Miranda et al, 2006; Ryan et al, 2010; Sohail et al, 2011; Olson et al, 2013a, 2013b; Wan et al, 2015). But the D genome of the first bread wheats were originated from only a small part of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Ae. tauschii worked as a gene repertoire for modern wheat adaptation (Jia et al, 2013; Li et al, 2014b), for their superiority in resistance to disease (Innes and Kerber, 1994; Cox et al, 1994; Yang et al, 2003; Miranda et al, 2006; Olson et al, 2013a, 2013b) and pest (Cox and Hatchett, 1994; Thompson and Haak, 1997; Zhu et al, 2005), tolerance to environmental stresses (Schachtman et al, 1991; Lan et al, 1997; Pritchard et al, 2002; Ryan et al, 2010; Sohail et al, 2011), and yield enhancement (Li et al, 2002; Huang et al, 2004; Kumar et al, 2007; Wan et al, 2015), all of which could be fixed as heterosis in hexaploid wheat theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Wang et al [ 17 ] mapped a QTL controlling leaf sheath hairiness on chromosome 4HL in an association mapping diversity panel of 569 barley cultivars using 1,042 SNP markers from the Illumina GoldenGate oligonucleotide pool assay 1 (BOPA1). Furthermore, Wan et al [ 18 ] detected a strong QTL on chromosome 4D associated with leaf sheath hairiness in wheat. The wild allele at this QTL originated from Aegilops tauschii , a wild progenitor of the hexaploid wheat, and was significantly associated with increased grain yield, grain weight and grain weight per spike [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wan et al [ 18 ] detected a strong QTL on chromosome 4D associated with leaf sheath hairiness in wheat. The wild allele at this QTL originated from Aegilops tauschii , a wild progenitor of the hexaploid wheat, and was significantly associated with increased grain yield, grain weight and grain weight per spike [ 18 ]. The authors suggested that DNA markers for leaf sheath hairiness could be used for marker-assisted selection to increase yield in wheat [ 18 ].…”
Section: Introductionmentioning
confidence: 99%